2011
DOI: 10.1111/j.1743-6109.2010.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and Metabolic Syndrome: A Meta-Analysis Study

Abstract: Introduction Metabolic syndrome (MetS) is often associated with male hypogonadism. Despite the well-known link, the role of testosterone replacement therapy (TRT) in MetS has not been completely clarified. Aim To systematically analyse the relationship between androgen levels and MetS we performed a review and meta-analyses of available prospective and cross-sectional studies. In addition, a specific meta-analysis on the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
244
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(269 citation statements)
references
References 70 publications
16
244
0
9
Order By: Relevance
“…As described in humans (Corona et al 2011a), MetS in rabbit was associated with a decline in testosterone and a rise in estrogen levels, which was normalized by testosterone, but not INT-747, dosing. As expected (Corona et al 2009, Zitzmann 2009, Corona et al 2011a,b, Traish et al 2011, sex steroid modifications were tightly associated with visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…As described in humans (Corona et al 2011a), MetS in rabbit was associated with a decline in testosterone and a rise in estrogen levels, which was normalized by testosterone, but not INT-747, dosing. As expected (Corona et al 2009, Zitzmann 2009, Corona et al 2011a,b, Traish et al 2011, sex steroid modifications were tightly associated with visceral fat accumulation.…”
Section: Discussionsupporting
confidence: 52%
“…Potential common etiological factors include hyperglycemia, insulin resistance, low-grade chronic inflammation (Moul & McVary 2010), and also hypogonadism (Pradidarcheep 2008). Recent data have in fact suggested that low testosterone in males might be considered an additional MetS component (Corona et al 2009, Zitzmann 2009, Corona et al 2011a,b, Traish et al 2011. Although testosterone supplementation in MetS significantly improves metabolic parameters (fasting glucose, glucose tolerance, waist circumference, triglycerides, and HDL cholesterol; Corona et al 2011a), concerns of potential prostatic side effects strongly limit a widespread clinical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in HDL cholesterol level was also observed, whereas no significant differences were observed for total cholesterol level, BP, or BMI. 67 In summary, the panel recommended:…”
Section: Recommended Assessments and Risk Clarificationmentioning
confidence: 99%
“…1 Obesity and insulin resistance (IR) have long been accepted as having a pivotal role in the etiopathogenesis of the syndrome. 2,3 However, emerging evidence indicates that even after controlling for these variables, there remains a substantial unexplained risk.…”
Section: Introductionmentioning
confidence: 99%